1995
DOI: 10.1093/oxfordjournals.eurheartj.a060747
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors of chronic heart failure in NYHA class II or III: value of invasive exercise haemodynamic data

Abstract: The population consisted of 32 men and 18 women. No gender-related differences were found. Two groups could be distinguished in terms of prognosis: G1: n = 31 living patients with no events, and G2: n = 19 deceased or with major events. G1 and G2 were comparable with regard to age, sex ratio and ejection fraction. Several of the 52 parameters tested were different in the two groups, in particular peak VO2, exercise duration, the workload developed during the cardiopulmonary test and all the invasive exercise h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
37
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 0 publications
2
37
0
1
Order By: Relevance
“…Exercise duration and peak VO 2 was not able to discriminate survivors from nonsurvivors. This was followed by the study of Roul et al 16 who showed that hemodynamic data measured at rest were weak predictors but cardiac power output and stroke work index measured at peak exercise were very strong predictors. Chomsky et al 8 in 185 patients with CHF found that the CO response to exercise was the most powerful predictor of survival in this study population according to both univariate and multivariate analyses.…”
Section: Discussionmentioning
confidence: 93%
“…Exercise duration and peak VO 2 was not able to discriminate survivors from nonsurvivors. This was followed by the study of Roul et al 16 who showed that hemodynamic data measured at rest were weak predictors but cardiac power output and stroke work index measured at peak exercise were very strong predictors. Chomsky et al 8 in 185 patients with CHF found that the CO response to exercise was the most powerful predictor of survival in this study population according to both univariate and multivariate analyses.…”
Section: Discussionmentioning
confidence: 93%
“…Resting and peak exercise cardiac power output has been shown to be a most powerful predictor of prognosis and mortality in patients with chronic heart failure and those with cardiogenic shock 32–36. Moreover, patients with a peak cardiac power output <2 W have a considerably higher mortality rate than those with a peak cardiac power output >2 W 34 36. Therefore, it is reasonable to suggest that patients with optimal HeartMate II LVAD support have a good long-term prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 The higher the pulmonary vascular resistance, the more the ventilation -perfusion inequality is aggravated. In the present study, none of the subjects had hypoxia before or after exercise testing, but would have developed hypoxemia if they continued to exercise after exhibiting aggravated ventilation -perfusion inequality.…”
Section: Discussionmentioning
confidence: 99%